Mechanism For Impeaching The Vice Regent Of Gorontalo Regency For The Period 2016-2020 - Asuki, Teddy Permana; Kadir, Yusrianto; Moonti, Roy Marthen; Bunga, Marten; Kasim, Muslim (International Journal of Sociology and Law, 2024)
The research aims at investigating he mechanism for impeaching the Vice Regent period for 2016-2020 Gorontalo district and factors that influence Vice Regent to be impeached. This research is empirical research or direct research. The research is used descriptive analysis method so that the comprehensive view picture can be obtained regarding the rules which related to applicable rules or norms. The impeachment process is starts begins with a report submitted by a society the Regional House of Representatives, which is the legislature's commissions. Then it was continued with the formation of a Special Committee to hold a plenary session of the impeachment process for the 2016-2020 Deputy Regent. From the final results of the process in the realm of the Regional People's Representative Council, it is submitted to the Supreme Court in Deciding and establishing an Opinion from the Regional People's Representative Council which is then validated by the Minister of Home Affairs and returned to the regional government to announce the decision on the dismissal. The legal basis for the process and prohibition of a leader is regulated in the 1945 Constitution in conjunction with Law number 23 of 2014 concerning regional government.